Atividade física de lazer e hábitos de vida de adultos vivendo em ambiente urbano - Janaina Lavalli Goston (2012)
Leisure-time physical activity (LTPA) is an important determinant of health. However, epidemiological studies indicate that a large portion of the population does not meet the current recommendations of at least 150 minutes/wk. In the public urban health context, understanding the factors associated with LTPA, in order to identify why some people areactive or inactive, has been the focus in promoting effective intervention strategies in populations. The data from two cross-sectional design studies, Saúde em Beagá (SBH) and Move-se Hemominas (MH) are presented in this thesis. The first study (SBH), which aimed to measure the prevalence and to identify the profile of LTPA, included 3,815 adults ( 18 years) who were living in two districts of Belo Horizonte/MG (Oeste and Barreiro). Additionally, the LTPA was investigated in relation to other health-related behaviors, including lifestyle and the social environment. In the SBH study, the prevalence of the recommended LTPA ( 150 min/week) was low (30.2%, n = 1,015). Out of them, the higher proportion was found among males with high participation in social activities (PS), and high social support for physical activity (PASS). Furthermore, males who have never smoked or were former smokers, who reported to regularly consume fruits / vegetables (FVL) ( 5 days/wk.), do not drink soda or add sugar to beverages, or opt for artificial sweeteners instead.Moreover, they were classified as having proper nutrition and better self-reported health perception. Due to the recognized influence of social factors on the behavior of health, 3,453 adults (18-69 years) were investigated in order to verify the specific associations between PASS and LTPA. Participants with higher PASS were more likely to achieve therecommended levels of LTPA. These results were characterized in single males, with higher education level and family income. In the second study (MH), the objective was to identify the association between occupational stress and health behaviors of 893 urban Brazilian civil servants (mean age: 40.2 years; 69.1% female), given that workplaces are supportiveenvironments for health changing habits. Healthy habits, such as physical activity (56%) and the consumption of fruits and vegetables (59.7%) were reported by employees. However, 49.4% were overweight. Workers with high levels of psychological demands, and low decision latitude (High-strain) were more active at work (PAW); while passive workers had less PA, and higher PAW. Although occupational stress and an unhealthy lifestyle (sedentary lifestyle, poor eating habits and smoking) may predispose a higher risk for chronic diseases (especially, cardiovascular disease), it was not possible in the MH study to confirm the effects of occupational stress on health-related behaviors of employees living in an urban environment. This result may suggest that adopting healthy habits and how people are faced with stressful life events may be associated with issues of social and physical environment. Finally, we must advance the understanding of healthy habits in an urban and occupational context, by exploring the individual, as well as the social and physical environment that can determine health-related behaviors, particularly the practice of physical activity